Development of Regenerative Agriculture in Gentinggunung Village, Sukorejo District, Kendal Regency - Muh. Sholeh; Nugroho Edi Kartijono; Dony Hidayat Al-Janan (Universitas Negeri Semarang, 2024)
Scarcity fertilizer subsidies and high costs non- subsidized fertilizer cause The Gunung Makmur Farmers Group is taking different alternatives, namely​ make fertilizer liquid organic in a way collective with utilise materials that are around​ they. See potential dirt livestock that has not been maximized and only used part small. Activities training making fertilizer has facilitated by Lazismu Kendal, the group farmer follow training making fertilizer liquid organic with facilitator practitioner agriculture Healthy from PT. Independent Earth Workshop. Aspect which become problem is related making fertilizer that is still use manual way, not yet use machine so that the production process is long and requires lots of energy, and conditions facility supporters who have not adequate. Activities devotion community that is done started from stage First that is preparation, doing licensing and survey field. Stage second that is activity devotion public through socialization about agriculture regenerative with method lectures, training making fertilizer organic through method practice directly. Stage third that is stage evaluation activity through method pre-test post-test. Evaluation results show that existence improvement knowledge farmer to agriculture regenerative and manufacturing fertilizer liquid. Farmers also participate participate in a way active in the process of activity discussion.